Effects of Nitroglycerine on Renal Ischemia-Reperfusion Injury in Adult Male Rats - Ahmadi, Fatemeh; Hajihashemi, Saeed; Rahbari, Ali; Ghanbari, Fatemeh (Drug Research, 2019)
Background Ischemia-reperfusion (I-R) leads to acute kidney injury (AKI). The present study investigated the effects of nitroglycerine (NG) on improving renal dysfunctions caused by I-R in rats.Methodology Twenty-four rats were equally divided into four groups: (1) the control group, (2) the sham group, (3) the I-R group, and (4) NG-treated groups.NG (50 μg/kg) was injected intraperitoneally after induction of IR. I-R was induced through clamping of the bilateral renal artery and vein of both kidneys for 20 min followed by 24 h of reperfusion.Results NG significantly increased the creatinine clearance levels and renal blood flow rate (which was reduced by I-R). NG also significantly improved serum electrolytes (sodium and potassium) that were disordered by I-R. In addition, NG significantly offset impaired antioxidant defense mechanism and inhibited lipid peroxidation.Conclusions The results show NG has a protective effect on renal tissue against AKI caused by I-R. These protective effects mediated through antioxidant activity and decrease of lipid peroxidation.
Keywords: nitroglycerine; renal ischemia-reperfusion injury; rat